Plasma potential correlations between heavy ion beam probe and langmuir probe on the Т-10 tokamak - Zenin, V.N.; Drabinskij, M.A.; Eliseev, L.G.; Grashin, S.A.; Khabanov, P.O.; Kharchev, N.K.; Krupnik, L.I.; Melnikov, A.V. (Вопросы атомной науки и техники, 2018)
This work is dedicated to simultaneous measurements of plasma potential oscillations at GAM frequencies in different locations on the T-10 tokamak and studying their correlation properties. Recent experiments with Heavy Ion Beam Probing and Langmuir probes have shown high coherency between signals of two diagnostics (up to 0.8) despite a large distance between the observation points: half of torus in toroidal and about π in poloidal direction, up to 12 cm in radial direction. The phase shift between potentials measured with two diagnostics has been obtained in two plasma scenarios. It was found the most likely that potential oscillations at the GAM frequency propagate outward, but influence of 2π phase shift cannot be excluded.